2001
DOI: 10.1046/j.0266-4909.2001.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

A problem‐solving based computer‐assisted tutorial for the earth sciences

Abstract: This study investigated the effects of a Problem‐Solving based Computer‐Assisted Tutorial (PSCAT) on earth science achievement and attitudes toward earth science of tenth graders (16‐year olds) in a senior high school in Taiwan. A total of 137 students who were enrolled in four earth science classes participated in this pre‐test/post‐test control‐group experiment. The experimental groups received the PSCAT; whereas the comparison groups received a Lecture‐Internet‐Discussion (LID) teaching approach. A multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…Some research found that CAI was effective in improving students' science achievement or their attitudes toward science (Chang, 2001a(Chang, , 2001b(Chang, , 2002Ferguson & Chapman, 1993;Levine, 1994;McCoy, 1991;Yalcinalp, Geban, & Ozkan, 1995). On the other hand, other researchers have found that the CAI approach has no significant effects on cognitive achievement or science learning (Morrell, 1992;Olugbemiro, 1991;Wainwright, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Some research found that CAI was effective in improving students' science achievement or their attitudes toward science (Chang, 2001a(Chang, , 2001b(Chang, , 2002Ferguson & Chapman, 1993;Levine, 1994;McCoy, 1991;Yalcinalp, Geban, & Ozkan, 1995). On the other hand, other researchers have found that the CAI approach has no significant effects on cognitive achievement or science learning (Morrell, 1992;Olugbemiro, 1991;Wainwright, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Much research in physics education has focused on the cognitive factors in developing effective pedagogical tools and assessment. For example, in physics and other related disciplines, tutorials (Chang, 2001;Singh et al, 2006;Wagner et al, 2006;Singh, 2008b;Zhu and Singh, 2011,b, 2013Brown and Singh, 2015;DeVore and Singh, 2015;Sayer et al, 2015;Singh and Marshman, 2015;DeVore et al, 2016a,b;Singh, 2016, 2017a,b,c), peer instruction (clicker questions with peer discussion) (Mazur, 1997), collaborative group problem solving with context-rich physics problems (Heller and Hollabaugh, 1992), POGIL (process-oriented guided-inquiry learning) activities (Farrell et al, 1999), etc. have been found effective in helping students learn (Shaffer and McDermott, 1992;Singh, 2009;Yerushalmi et al, 2012a,b;Stewart et al, 2016;Wood et al, 2016).…”
Section: Factors 1 and 2: Internal Characteristics Of Learning Tools mentioning
confidence: 99%
“…Computer-Aided Learning is not a solitary computer learning system, but part of an instructive approach devised to educate a specific subject (Joint, 2003;Tucker, 1997). Computer-Assisted Instruction provides a vehicle for providing extended practice to increase learner's ability (Chang, 2001). Cepni, Tas, and Kose (2006) found Computer-Assisted Instruction materials can improve student achievement, change misconceptions in some degree, and progress cognitive levels in science education domain.…”
Section: E-learningmentioning
confidence: 99%